The systemic regulation of credit rating agencies and rated markets - Sy, Amadou N. R. (IMF working paper ;, 2009)
Credit ratings have contributed to the current financial crisis. Proposals to regulate credit rating agencies focus on micro-prudential issues and aim at reducing conflicts of interest and increasing transparency and competition. In contrast, this paper argues that macro-prudential regulation is necessary to address the systemic risk inherent to ratings. The paper illustrates how financial markets have increasingly relied on ratings. It shows how downgrades have led to systemic market losses and increased illiquidity. The paper suggests the use of "ratings maps" and stress-tests to assess the systemic risk of ratings, and increased capital or liquidity buffers to manage such risk